Economic analysis of foot and mouth disease on cattle farming and lifestock industry in Malaysia - Mohamad, Abdullah (2019)
The cattle industry plays an essential role in Malaysia’s economic development. Despite its significant contribution to the economy (i.e. sources of protein, income and asset base to the farmers), the industry is undeniably vulnerable to the infection and diffusion of foot and mouth disease (FMD). To eradicate the FMD outbreak and improve the productivity of Malaysia’s livestock, the Malaysian Good Agricultural Practices (MyGAP) scheme was implemented. Despite of that, Malaysian cattle industry is continuously challenged by the frequent FMD outbreak, shortage in domestic supply, low self-sufficiency level (SSL), high dependency on the imported meat and significant price fluctuations. Being considered as an economic problem, the FMD outbreak cause losses to the country’s economy if it is not tackled correctly. Based on the above background, in general this study analyzed economic impact of FMD on the cattle farming and livestock industry in Malaysia. In specific, this study examined the impact of FMD on the meat price and margin. It also estimated the mortality and weight losses of cattle due to FMD and assessed the impact of practice of MyGAP knowledge in sustaining cattle farming during and after FMD outbreak. To achieve the objectives of the study, primary and secondary data were used. Primary data was collected using snowball sampling technique from 355 local cattle farms in Peninsular Malaysia who were affected by FMD. By using a set of questionnaires, the data were collected in six states of Peninsular Malaysia (i.e. Kelantan, Pahang, Selangor, Malacca, Negeri Sembilan and Johor) from April 2018 until October 2018. The secondary data (i.e. Malaysia meat prices and number of FMD cases) was obtained from the Federal Agricultural Marketing Authority (FAMA) and the Southeast Asia Foot and Mouth Disease (SEAFMD) database, respectively. To analyze the data, three methods were used; viz. time series analysis, economic valuation analysis and propensity score matching technique (PSM). Firstly, the time series analysis was used to evaluate the impact of FMD outbreak on the meat prices, price margin and interdependence of meat prices. Economic valuation analysis was then used to estimate mortality and weight losses due to FMD. Finally, the PSM was used to assess the impact of practice of MyGAP knowledge in sustaining cattle farming during and after FMD outbreak. For the first objective, the results showed that meat prices, margin and interdependence of each price in Malaysia significantly change differently due to the FMD outbreak. While for the second objective, Peninsular Malaysia cattle industry suffers mortality and weight losses due to the outbreak of FMD. For the third objective, practice of MyGAP knowledge helps cattle farmers sustain their production during and after the FMD outbreak. In conclusion, to reduce and eradicate the FMD impact and improve the productivity as well as the quality of Malaysia cattle industry in line with the international standards, the government should be actively enforced MyGAP to be practiced by all cattle farmers as the study found that MyGAP offer benefits to farmers. For future research, it’s recommended that the researcher emphasis more on the surveillance issues as it is a vital procedure to eradicate FMD outbreak.